Optimal control of distributed bilinear systems - Banks, S.P. (Systems & control letters, 1987)
The optimal control problem for a bilinear distributed parameter system subject to a quadratic cost functional is solved. It is shown that the optimal control is given by a convergent power series in the state with tensor coefficients.